Indole-3-carbinol induces apoptosis of chronic myelogenous leukemia cells through suppression of STAT5 and Akt signaling pathways. Issue 6 (May 2017) - Safa, Majid; Jafari, Leila; Alikarami, Fatemeh; Manafi Shabestari, Rima; Kazemi, Ahmad
Signal transducer and activator of transcription 5 and Akt pathways, implicated in signaling transduction downstream of BCR–ABL, play critical roles in the pathogenesis of chronic myeloid leukemia. Therefore, identification of novel compounds that modulate the activity of such pathways could be a new approach in the treatment of chronic myeloid leukemia. Previous studies have demonstrated that indole-3-carbinol inhibits the proliferation and induces apoptosis of various tumor cells. However, its anticancer activity against chronic myeloid leukemia cells and the underlying mechanism remain unclear. Our data revealed that indole-3-carbinol promoted mitochondrial apoptosis of chronic myeloid leukemia–derived K562 cells, as evidenced by the activation of caspases and poly (ADP-ribose) polymerase cleavage. Treatment with indole-3-carbinol was found to be associated with a decrease in the cellular levels of phospho-Akt and phospho–signal transducer and activator of transcription 5. In addition, real-time polymerase chain reaction analysis showed that the downregulation of genes is regulated by Akt and signal transducer and activator of transcription 5. We also found that treatment with indole-3-carbinol resulted in the activation of the p38 mitogen-activated protein kinase and reduced expression of human telomerase and c-Myc. Collectively, these results demonstrate that the oncogenic signal transducer and activator of transcription 5/Akt pathway is a cellular target for indole-3-carbinol in chronic myeloid leukemia cells. Thus, this clinically tested natural compound can be a potential candidate in the treatment of chronic myeloid leukemia following confirmation with clinical studies.